Variation in cognitive function over time in Gaucher disease type 3 - Steward, Alta M. (Neurology, 2019)
OBJECTIVE: To identify relevant efficacy parameters essential in designing clinical trials for brain-penetrant therapies for Gaucher disease, we evaluated cognitive function longitudinally in 34 patients with Gaucher disease type 3 seen at the NIH Clinical Center. METHODS: Individuals were tested with age-appropriate Wechsler Intelligence Scales administered between 1 and 18 times over 29 years. Variation in all IQ domains was not linear with time and was best characterized with the coefficient of variation (SD/mean) for each individual. Mixed-effects regressions were used to determine whether IQ was associated with clinical features. Models were controlled for variation in test version, participant identification, and test administrator. RESULTS: Mean verbal, performance, and full-scale IQs were 81.77, 75.98, and 82.02, respectively, with a consistent discrepancy between verbal and performance IQs. Mean (SD) verbal, performance, and full-scale coefficient of variations were 0.07 (0.04), 0.09 (0.05), and 0.06 (0.02), respectively. IQ varied about a mean, with no clear trajectory, indicating no clear patterns of improvement or decline over time. EEG lateralization and behavioral issues were consistently associated with IQ. CONCLUSIONS: The observed variation in IQ in Gaucher disease type 3 across the cohort and within single individuals over time may be characteristic of other neuronopathic diseases. Therefore, to reliably use IQ as an efficacy measure in any clinical trial of neurotherapeutics, a normal variation range must be established to assess the clinical relevance of any IQ change.